(untitled) (European Journal of Pure and Applied Mathematics, 2015)
In this paper we introduce and investigate a new class of strong continuous functions called strongly Î¸-Î´-Î²-continuous functions by using two new strong forms of Î´-Î²-open sets called Î´-Î²-regular sets and Î´-Î²Î¸-open sets. This class is a generalization of both strongly Î¸-e-continuous functions and strongly Î¸-Î²-continuous functions. Severalnew characterizations and fundamental properties concerning strongly Î¸-Î´-Î²-continuous functions are obtained. Furthermore, the relationships between strongly Î¸-Î´-Î²-continuous functions and other well-known types of strong continuity are also discussed. Â Â Â